Outcome of Combined Periodontal-Orthodontic Treatment of Pathologic Tooth Migration: A Longitudinal Study - Sahibzadi Fatima Tariq, Mohammad Aun Ali Mehdi, Shazmeen Zahra, Taimur Khan, Samir Azeem, Hijab Farid (Pakistan Journal of Medical & Health Sciences, 2023)
Introduction: A number of periodontal bone abnormalities, most of which are horizontal, have been associated with flared and long incisors. Individuals with anterior incisor displacement and periodontal disease may benefit from orthodontic-periodontal therapy. Objective: To determine the outcome of combined periodontal-orthodontic treatment of pathologic tooth migration Study design: A longitudinal study Place and Duration: This study was conducted at Rehman college of dentistry Peshawar, Pakistan from February 2022 to July 2022 Methodology: A 4-person team designed the study’s procedures. On 56 maxillary incisors with horizontal bone anomalies, this surgery was performed to remove circumferential supracrestal fibrotomy and orthodontic-periodontal therapy. To compensate for the angular bone shortage in front teeth treated with orthodontics, guided tissue regeneration and periodontal regenerative surgery were performed. Before, throughout, and six months after guided tissue regeneration treatment (T1), cone-beam computed tomography images were done (T2). At each of the first three time points, the depth of the probing pocket and the degree of clinical attachment loss were determined. Paired t-tests were used to analyse the data. Results: Clinical attachment loss decreased by 0.28 mm from T0 to T1 (P <0.05). The distance between the cementoenamel junction and the bone top decreased by 0.65 mm (P <0.05). Alveolar bone thickness decreased by 0.45 mm on both the lingual and labial sides of the bone (P<0.05). Bone anomalies in some teeth have been converted from horizontal to vertical. From T1 to T2, radiographic testing revealed a 2.16 mm vertical and 1.45 mm horizontal bone redeposition (P<0.05), as well as improvements in probing pocket depth and clinical attachment loss (P<0.05). During combination therapy, the cementoenamel distance decreased from 2.10 mm to 1.31 mm (P <0.05). Conclusion: We were able to address periodontal diseases caused by improper bone implantation by combining orthodontic and periodontal treatment. By altering the bone structure, it is possible to improve the outcome of directed tissue regeneration following orthodontic invasion with fibrotomy. Keywords: orthodontic and periodontal treatment, outcome, bone implantation, Periodontal disease